2018
DOI: 10.15406/aaoaj.2018.02.00047
|View full text |Cite
|
Sign up to set email alerts
|

Design methodology for hybrid (VTOL + Fixed Wing) unmanned aerial vehicles

Abstract: The evolution in the missions' complexity of both military aircraft and Unmanned Aerial Vehicles (UAVs) and the increase in civilian air-traffic, with limited runways, have led to the development of a new category of aircraft called Transitional Aircraft (TA). The goal of TA is to take advantages of both the characteristics of fixed-wing aircraft, like high speed, range and endurance, and of rotorcraft such as hovering, low-speed flight and Vertical Takeoff and Landing (VTOL). Despite the abundant knowledge on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Hybrid fixed-wing/multi-rotor UAVs combine the aspects of a multi-rotor and a fixed-wing aircraft [127], [128], [129]. These aircraft utilize both an airfoil and downward thrust to combine the VTOL capabilities of a multi-rotor with the higher efficiency of a fixedwing aircraft.…”
Section: ) Hybrid Fixed-wing/multi-rotor Uavsmentioning
confidence: 99%
“…Hybrid fixed-wing/multi-rotor UAVs combine the aspects of a multi-rotor and a fixed-wing aircraft [127], [128], [129]. These aircraft utilize both an airfoil and downward thrust to combine the VTOL capabilities of a multi-rotor with the higher efficiency of a fixedwing aircraft.…”
Section: ) Hybrid Fixed-wing/multi-rotor Uavsmentioning
confidence: 99%
“…e results showed that the error was less than 3%. Finally, the proposed approach can be utilized to calculate optimized power requirements, wing loading, and rotor disc loadings based on actual flight mode requirements [26]. Muraoka e plan was to use the model for the analysis of flight characteristics, namely, trim, transition schedule, stability, and controllability.…”
Section: Tilt Wing Vtol Uavmentioning
confidence: 99%
“…To control yaw, at least one (occasionally two) of the three rotors is operated to pivot and generate torque. The actuation forces are non-trivial due to gyroscopic forces generated by the fast-spinning motors [9].…”
Section: Fig 1 -Vtol In Hover Flight [1]mentioning
confidence: 99%